Perceptions, Perceived Efficacy, and Factors Influencing the Objective Structured Clinical Examination Among Nursing Students at the University of Ibadan - Chizoma Ndikom (The Nursing Scope, 2026)
Background: The Objective Structured Clinical Examination (OSCE) has been widely adopted in health professions education because of its objectivity, standardisation, and structured approach to assessing clinical competence. Despite its widespread use, limited evidence exists regarding nursing students’ perceptions of the OSCE, its perceived efficacy, and the factors influencing their performance. Aim: To assess nursing students’ perceptions, perceived efficacy, and factors influencing performance in the Objective Structured Clinical Examination. Method: A cross-sectional descriptive study was conducted among 135 nursing students in 300–500 levels who had prior OSCE experience at the University of Ibadan. Participants were selected using stratified random sampling. Data were collected using a structured, self-administered questionnaire adapted from validated instruments and administered through Google Forms. The questionnaire assessed respondents’ demographic characteristics, perceptions of the OSCE, perceived efficacy, and factors influencing performance. Data were analysed using descriptive statistics (frequencies, percentages, means, and standard deviations) and Fisher’s exact test at a 5% level of significance (α = .05). Findings: The respondents had a mean age of 22.96 ± 1.86 years, and the majority were female (83.7%). Most respondents perceived the OSCE as a fair method of assessment (65.9%). Participants reported that the OSCE effectively assessed a broad range of clinical skills (73.3%) and aligned well with taught course content (69.6%). Major factors influencing performance included examiner behaviour (73.3%), examination anxiety (94.8%), inadequate time allocation (82.2%), and improvised equipment (83.0%). Time allocation (p = .037) and content load (p = .028) were significantly associated with students' perceptions of OSCE performance. Conclusion: The OSCE is perceived as an effective and objective method for assessing clinical competence among nursing students. However, inadequate time allocation, unfavourable examiner behaviour, examination anxiety, and insufficient resources may adversely affect students' performance and the overall effectiveness of the examination. Recommendation: Nursing education institutions should strengthen examiner training, ensure adequate availability of standard equipment and materials, optimise time allocation for OSCE stations, and review checklist structures to improve assessment quality, enhance students' performance, and promote clinical competence. Keywords: Objective Structured Clinical Examination (OSCE), clinical competence, efficacy, influencing factors, nursing students, perception.